2015
DOI: 10.1016/j.biortech.2015.07.072
|View full text |Cite
|
Sign up to set email alerts
|

Comparative techno-economic assessment and LCA of selected integrated sugarcane-based biorefineries

Abstract: h i g h l i g h t sThe four scenarios can show a 56-70% reduction in GHG emissions. Furthermore a 51-57% reduction in Fossil depletion impact is estimated. The benefits of the other investigated environmental impacts are limited. The four scenarios are energy self-sufficient. Integrated sugarcane biorefineries can be economically efficient. This work addresses the economic and environmental performance of integrated biorefineries based on sugarcane juice and residues. Four multiproduct scenarios were considere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(31 citation statements)
references
References 19 publications
1
28
0
2
Order By: Relevance
“…This method was synthesized in four interrelated phases: goal and scope definition, inventory analysis, impact evaluation, and interpretation [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…This method was synthesized in four interrelated phases: goal and scope definition, inventory analysis, impact evaluation, and interpretation [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…Some useful parameters that can be used to calculate the economic assessment of a biorefinery are capital cost (or fixed capital investment), operating cost (operating expenses), net present value (NPV), return on investment (ROI), discounted payback period (DPBP), payback period (PBP), internal rate of return (IRR), and gross margin (or economic margin, profit margin), which can be estimated using computer programs such as economic analyzers . Plant capacity and mass and energy balances are the basis for the estimation of costs.…”
Section: Economic Assessmentmentioning
confidence: 99%
“…A companion study on the energetic and environmental performances of different biomass technologies concluded that the highest EEs were obtained in the case of integrated solid fuel and biogas from biomass 23 . Strong environmental and economic performance has also been documented from integrated bioenergy plants relative to standalone bioenergy plants 24–28 . With regard to EROIs, several studies concluded that biofuels and bioenergy are net energy providers 29–31 .…”
Section: Introductionmentioning
confidence: 99%